2003
DOI: 10.1080/01443610310001604457
|View full text |Cite
|
Sign up to set email alerts
|

The use of simple ketamine anaesthesia for day-case diagnostic laparoscopy

Abstract: General anaesthesia using ketamine has been shown to be safe. It is generally used in our private hospitals where there is lack of qualified personnel and sophisticated anaesthetic machines. A retrospective review of 295 cases of laparoscopy was performed over 28 months at the fertility Unit of Life Specialist Hospital Nnewi, Anambra State, Nigeria. Ketamine general anaesthesia was used for all the patients after premedication with 0.6 mg of atropine. Seventy-six and 102 patients who had additional premedicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…All the procedures were performed following an overnight fast and under ketamine general anesthesia by the author. [4] During the procedure, the patient is anesthetized and placed in lithotomy trendelenburg position. The abdomen, perineum, and vagina are cleansed and draped leaving only the umbilical area and the vulva.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the procedures were performed following an overnight fast and under ketamine general anesthesia by the author. [4] During the procedure, the patient is anesthetized and placed in lithotomy trendelenburg position. The abdomen, perineum, and vagina are cleansed and draped leaving only the umbilical area and the vulva.…”
Section: Methodsmentioning
confidence: 99%
“…It is performed to evaluate the female reproductive system or other gynecological complaints like chronic pelvic pain. [1][2][3] Diagnostic laparoscopy is traditionally done in operating theatre under general anesthesia; [4] though there has been reports of use of local anesthesia with sedation for office laparoscopy. [5,6] The procedure takes between 20 and 30 min and the patients are usually discharged from the hospital the same day.…”
Section: Introductionmentioning
confidence: 99%
“…Although concerns are often expressed regarding the effect of anesthetics on experimental results, it has been demonstrated that general anesthesia using ketamine is safe and effective (Ikechebelu et al 2003). In this study, the ketamine dose was kept as low as possible for the purposes of physiological observation.…”
Section: Resultsmentioning
confidence: 99%
“…[6,20] However, in developing countries like Nigeria, Ikechebelu and colleagues reported that ketamine is still commonly used in private hospitals where there is lack of qualified anesthetists and facilities. [21] Therefore, they suggested that ketamine could safely be used as it produces effective simple anesthesia, especially for day case laparoscopies.…”
Section: Anesthesia For Day Surgerymentioning
confidence: 99%